Craving for poetry: 18th-century poets’ views on the uncontrollable desire to write poetry - Николаев, Сергей (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The penchant for writing poetry became a prominent discussion topic among Russian poets at the very beginning of the 18th century. While poets would usually exonerate themselves of their own “wretched inclination” to versify profusely, they would ridicule and judge similar proclivities shown by fellow poets: as Feofan Prokopovich put it, Omnes ad nauseam versificari occeperant (“everyone was composing verses in the most annoying way”). This kind of criticism was not unfounded: prolific writing led to a deterioration in style, loss of literary craft, dilettantism, and an overall decline in the prestige of the profession. Another consequence was the rise of graphomania that was likewise found reprehensible in literary polemics. Using many case studies, the author of the paper argues that these debates were closely tied to the formation of the literary culture of Modern Times, to changes in daily literary life and to the development of the image of a writer which for the most part would remain unchanged until the present.